REGISTRATION OF THE VISITS OF PHOENICOPTERUS CHILENSIS (MOLINA, 1782) TO THE WETLANDS OF THE CALLAO REGION, PERÚ - Carazas, Nestor (2019)
The visit of Phoenicopterus chilensis (Molina, 1782) to the wetlands of the Callao Region, Peru from April to January is reported in variable numbers from one to 14 individuals. The observations were made of adults, juveniles and immatures. The oldest record for these wetlands is the one reported in August 1998 by Edward Brinkley and the largest; record of P. chilensis was in August 2017 with 14 individuals.